2004
DOI: 10.1063/1.1765834
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the vortex formation process behind a heated cylinder

Abstract: This paper describes the three-dimensional (3D) vortex formation process behind a heated cylinder at low Reynolds numbers. Both experimental and numerical techniques are used, including an electrochemical tin-precipitation visualization method, a two-dimensional (2D) high resolution particle velocimetry technique, and a 3D spectral element method. The wake flow is simultaneously investigated in two perpendicular planes using a “dual-plane” configuration. It appears that for Reynolds number around 100 and Richa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Dumouchel et al [23] studied the transition from a two-dimensional (2-D) steady to a 2-D periodic wake at Re ¼ 52-61 of air. Kieft et al [24,25], Steenhoven and Rindt [26], and Ren et al [27] studied experimentally and numerically three-dimensional (3-D) vortex formation behind a heated cylinder at Re ¼ 75, 75, 100, and 100. Mass et al [28] visualized 3-D vortex formation behind a heated cylinder at Re ¼ 117 by an electrochemical tin precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Dumouchel et al [23] studied the transition from a two-dimensional (2-D) steady to a 2-D periodic wake at Re ¼ 52-61 of air. Kieft et al [24,25], Steenhoven and Rindt [26], and Ren et al [27] studied experimentally and numerically three-dimensional (3-D) vortex formation behind a heated cylinder at Re ¼ 75, 75, 100, and 100. Mass et al [28] visualized 3-D vortex formation behind a heated cylinder at Re ¼ 117 by an electrochemical tin precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the experiments and calculations have been quantitatively compared in Ref. 16. There, a good agreement has been achieved between the experimentally measured and numerically calculated velocity fields in the ͑X-Y͒ plane at "in-plume" ͑spanwise position where the plume escapes downstream͒ and "out-of-plume" ͑spanwise position where no plume escapes downstream͒ positions, validating the numerical approach.…”
Section: D Spectral Element Methodsmentioning
confidence: 49%
“…15 The influence of these near-wake flow phenomena on the vortex shedding process is investigated in Ref. 16. It is shown that quite large differences occur between the different spanwise positions.…”
Section: Introductionmentioning
confidence: 99%
“…Escaping mushroom-type structures occur in the far wake with a spanwise distance of around twice the cylinder diameter. 12 Furthermore, it has also been shown in Ref.…”
Section: Introductionmentioning
confidence: 80%
“…12 Figure 6 shows a top view of the wake flow pattern, obtained by means of the tin-precipitation visualization technique. The flow is from bottom to top and the gravity direction is in the negative y direction.…”
Section: Coherent Structures In the Flow Fieldsmentioning
confidence: 99%